Front Matter Vol. 11 No. 2 2018 - Statistika, Media (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2018)
Cover dan Daftar Isi Media Statistika Vol. 11 No. 2 Desember 2018